Iocasia fonsfrigidae NS-1 gen. nov., sp. nov., a Novel Deep-Sea Bacterium Possessing Diverse Carbohydrate Metabolic Pathways - Zhang, Jing; Zhang, Yuechao; Liu, Rui; Cai, Ruining; Liu, Fanghua; Sun, Chaomin (Frontiers in Microbiology, 2021)
Resolving metabolisms of deep-sea microorganisms is crucial for understanding ocean energy cycling. Here, a strictly anaerobic, Gram-negative strain NS-1 was isolated from the deep-sea cold seep in the South China Sea. Phylogenetic analysis based on 16S rRNA gene sequence indicated that strain NS-1 was most closely related to the type strain Halocella cellulosilytica DSM 7362T (with 92.52% similarity). A combination of phylogenetic, genomic, and physiological traits with strain NS-1, was proposed to be representative of a novel genus in the family Halanaerobiaceae, for which Iocasia fonsfrigidae NS-1 was named. It is noteworthy that I. fonsfrigidae NS-1 could metabolize multiple carbohydrates including xylan, alginate, starch, and lignin, and thereby produce diverse fermentation products such as hydrogen, lactate, butyrate, and ethanol. The expressions of the key genes responsible for carbohydrate degradation as well as the production of the above small molecular substrates when strain NS-1 cultured under different conditions, were further analyzed by transcriptomic methods. We thus predicted that part of the ecological role of Iocasia sp. is likely in the fermentation of products from the degradation of diverse carbohydrates to produce hydrogen as well as other small molecules, which are in turn utilized by other members of cold seep microbes.